Trade Wars in Global Politics: An Analysis of Propaganda and Its Impact on International Relations and the Global Economy - Najla Shafaa Kamila; Devah Sukmawati; Umar Gibran Asshiddiqi (Penerbit Hellow Pustaka, 2025)
Trade wars have become a global phenomenon that affects international relations and the global economy. This article aims to analyze the propaganda used in trade wars and their impact on international relations and the global economy. This study uses content analysis methods and case studies to analyze the data. The results of the study show that propaganda is used as a tool to influence public opinion and strengthen the country's position in the trade war, thus causing international relations tensions, a decline in global trade, and economic instability.